Evaluasi Sosial-Teknis Nature-Based Solutions dalam Pengelolaan Limpasan pada Sistem Drainase Kawasan Pemukiman Berbasis Pemodelan EPA SWMM - Willy Cahyadhiputra Gunawan; Eriani Ramadhianti; Ghidan Satya Kesuma; Moch Nabil Nugraha; Muhammad Tsaabitah Haulidan Putra; Rindu Damayanti; Nayla Hanna Ariza (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
The expansion of built-up areas in residential environments increases impervious surface coverage, reduces infiltration capacity, and intensifies surface runoff. This condition highlights the need for drainage management approaches that do not rely solely on conventional channels but also incorporate Nature-based Solutions (NbS) to control stormwater at its source. This study evaluates the effectiveness of NbS in reducing surface runoff within the drainage system of the Sulaiman Air Force Base residential complex, Bandung Regency. The hydrological analysis included the calculation of design rainfall for a 5-year return period, rainfall intensity using the Mononobe method, and design discharge using the Rational Method. Hydraulic analysis of the drainage channels was conducted using Manning’s equation. The drainage system was evaluated using EPA SWMM under three scenarios: the existing drainage condition, drainage with NbS implementation, and drainage integrating NbS with storage. The NbS elements analyzed included bioretention cells, rain gardens, rain barrels, and storage facilities. The results show that NbS implementation can reduce peak runoff compared with the existing condition. The integration of NbS and storage produced the best performance by retaining runoff, increasing infiltration, and reducing the flow burden on the drainage network.